2015
DOI: 10.1007/s11682-015-9368-6
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary volumes are changed in patients with conversion disorder

Abstract: Our study group previously measured pituitary volumes and found a relationship between somatoform disoders and pituitary volumes. Therefore, in conversion disorder, another somatoform disorder, we hypothesized that pituitary gland volumes would be reduced. Twenty female patients and healthy controls were recruited to the present investigation. The volumes of the pituitary gland were determined by using a 1.5 Tesla magnetic resonance scanner. We found that the pituitary gland volumes of the patients with conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
0
15
0
3
Order By: Relevance
“…Since the 19th century, it has been considered that there was no anatomic and functional pathology in the brains of patients with conversion disorder, and the absence of abnormal findings in imaging results was a supportive factor in the diagnosis of FND for the clinician. In recent years, however, study findings indicated structural and functional changes in regions of the brain associated with the symptoms [1,[3][4][5][6][7][8][26][27][28]. Corpus callosum provides integration between the hemispheres by connecting related cerebral cortex regions in the brain [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the 19th century, it has been considered that there was no anatomic and functional pathology in the brains of patients with conversion disorder, and the absence of abnormal findings in imaging results was a supportive factor in the diagnosis of FND for the clinician. In recent years, however, study findings indicated structural and functional changes in regions of the brain associated with the symptoms [1,[3][4][5][6][7][8][26][27][28]. Corpus callosum provides integration between the hemispheres by connecting related cerebral cortex regions in the brain [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of one or more voluntary, motor or sensory function changes and incompatibility and discrepancy between neurological or general medical conditions that may explain this appearance are included in the diagnostic criteria [2]. Although the findings reported in structural and functional brain imaging studies available in the literature did not sufficiently explain the physiopathology of FND [3], certain studies suggested and supported the presence of significant brain findings accompanying FND symptoms [1,[3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literatürde eski tarihli yazılarda bedensel semptomlarla ortaya çıkan psişik bozuklukların daha önceki ruhsal travmaların fiziksel etkileri olarak meydana geldiğinden bahsedilirken (23), son zamanlarda KB semptomlarının spesifik yapısal (anatomik) ve fonksiyonel beyin korelasyonları gösterilmeye başlanmıştır (9,12,13). Yapısal beyin görüntüleme çalışmaları (bilgisayarlı tomografi, BT; manyetik rezonans görüntüleme, MRG ) beynin anatomisi hakkında bilgi verirken (9) fonksiyonel görüntüleme çalışmaları ise (tek foton emisyon tomografi, SPECT) beynin canlı etkinliği ve aktivitesi hakkında bilgi vermektedir (8).…”
Section: Discussionunclassified
“…Çalışmalardan elde edilen bulgular toplu olarak, KB olan hastalarda önemli beyin bulgularının eşlik edebileceğini düşündüren ve destekleyen niteliktedir (6)(7)(8)(9)(10)(11)(12)(13). KB tanılı hastalarda yapılan görüntüleme çalışmalarında KB ile yapısal beyin anormallikleri arasında ilişki olabileceği bulgularının varlığı (5,7,12,13) daha spesifik alanların detaylı incelenmesine ihtiyaç duyulduğunu göstermektedir. Bu tür bulguların ilerisi için olası etkisi sınıflandırma sistemlerinde KB'nun tanımlanma biçimi üzerine olabilir.…”
Section: Discussionunclassified